2012
DOI: 10.7883/yoken.65.326
|View full text |Cite
|
Sign up to set email alerts
|

A Superior Test for Diagnosis of Clostridium difficile-Associated Diarrhea in Resource-Limited Settings

Abstract: SUMMARY:In this prospective cohort study, we investigated the prevalence of Clostridium difficileassociated diarrhea (CDAD) in adult patients with nosocomial diarrhea by performing enzyme immunoassay (EIA) for detecting toxins A and B and polymerase chain reaction (PCR) for detecting the presence of the tcdB gene in stool samples. We determined the factors associated with CDAD, and the treatment outcome of CDAD from May 2010 to January 2011. A total of 175 stool samples were tested by EIA and PCR. In total, 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Of 54 PCR-positive samples, 7 were tcdA +    tcdB +    cdtA / B + , 13 were tcdA +    tcdB +    cdtA / B − , 30 were tcdA −    tcdB +    cdtA / B − , and 4 were tcdA −    tcdB +    cdtA / B − . Although, there are previous reports on C. difficile toxin types in Thailand [24, 25], this is the first time that the tcdA +    tcdB +    cdtA / B + isolates were detected. It is also noteworthy that PCR detection of C. difficile toxin genes might only detect DNA without the presence of toxin production; therefore, the PCR-positive cases should be carefully interpreted.…”
Section: Resultsmentioning
confidence: 83%
“…Of 54 PCR-positive samples, 7 were tcdA +    tcdB +    cdtA / B + , 13 were tcdA +    tcdB +    cdtA / B − , 30 were tcdA −    tcdB +    cdtA / B − , and 4 were tcdA −    tcdB +    cdtA / B − . Although, there are previous reports on C. difficile toxin types in Thailand [24, 25], this is the first time that the tcdA +    tcdB +    cdtA / B + isolates were detected. It is also noteworthy that PCR detection of C. difficile toxin genes might only detect DNA without the presence of toxin production; therefore, the PCR-positive cases should be carefully interpreted.…”
Section: Resultsmentioning
confidence: 83%
“…Toxigenic culture, which is a current reference standard for C. difficile detection, is rarely performed these days because of time and cost constraints, while the use of PCR-based techniques has increased over the years [7]. In addition to a lack of an optimal detection method, the most recent prevalence study was conducted between 2010 and 2011 [10] and the most recent molecular epidemiologic study between 2006 and 2008 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study in Bangkok found that combining toxin EIAs with direct tcdB PCR on stool increased positive diagnoses two-fold, compared with toxin EIAs alone [54]. …”
Section: Introductionmentioning
confidence: 99%